The practice of armed struggle of the Organización Popular Revolucionária – 33 Orientales in Uruguay (1968-1972) - Viana, Rafael (Revista Crítica Histórica, 2022)
This article aims to analyze the formation, conception and armed action of the Organización Popular Revolucionária – 33 Orientales (OPR-33), the armed wing of the Federación Anarquista Uruguaya, which operated mainly on Uruguayan soil and was later transferred to Argentina. In this article, we will analyze the organization’s armed actions on Uruguayan soil and its relationship with social and union struggles in that country, in the context of the hardening of the constitutional regime. Against the backdrop of the Cuban Revolution, the action of the rights in Uruguay and the formation of a guerrilla grammar in the country, the article intends to elucidate the practice of OPR-33 from case studies.